Sensor based Human Assistance System - D. , Charansai; P. , Shyamala Bharathi (International Journal of Psychosocial Rehabilitation, 2020)
Right now we are going to structure a robot that follows man. These days, robots assume a fundamental job in human life. Numerous looks into the field of mechanical technology so as to lessen the workload of people. On the off chance that this succeeds, the robots will be utilized in everyday applications alongside people. Indeed, even in enterprises and in emergency clinics, we are wanting to utilize robots to support people. The principal testing idea is that the robot that we are planning ought to adhere to the guidelines given by people; if this succeeds, everything will be right in a robot instrument. Here we have planned a robot that will really take a shot at an ultrasonic sensor. This will recognize the human and begin tailing him. As this is the initial step, we can build up a decent robot in the upcoming works.